Stances of the Narratee - Diana Achim (Journal of Humanistic and Social Studies, 2012)
The issue of the narratee has not been thoroughly studied by literary theorists. More exactly, it is approached tangentially, due to the necessity of keeping the symmetry of the instances considered important – author, narrator, character, reader. The study of the narratee is an interesting exercise of reading a literary work “upside down”. In the context of the literary discourse theory, the narratee bears resemblance to Cinderella. Overshadowed, it supports through its functions the complicated mechanism of conveying the message from the narrator to the concrete reader, it mediates, filters, connects the unseen threads of history and discourse, it is attentive, receptive, active because, metaphorically speaking, the pointed shoe of the story told by the narrator fits only the narratee.